2017
DOI: 10.1111/cea.12897
|View full text |Cite
|
Sign up to set email alerts
|

The sensitization pattern differs according to rhinitis and asthma multimorbidity in adults: the EGEA study

Abstract: Allergic sensitization and particularly polysensitization rates widely differ according to asthma and rhinitis status. This study emphasized the importance of taking into account multimorbidity between asthma and rhinitis and showed that allergic sensitization is not a dichotomic variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 33 publications
7
43
1
3
Order By: Relevance
“…Among subjects aged 20‐40 years in the 2006 cohort, 83% of those reporting allergic rhinitis had elevated specific IgE levels to any allergen which implies that ARC was a good marker for allergic sensitization . Our definition of allergic asthma is also supported by a recent publication where 65% of subjects with asthma and ARC were polysensitized …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Among subjects aged 20‐40 years in the 2006 cohort, 83% of those reporting allergic rhinitis had elevated specific IgE levels to any allergen which implies that ARC was a good marker for allergic sensitization . Our definition of allergic asthma is also supported by a recent publication where 65% of subjects with asthma and ARC were polysensitized …”
Section: Discussionsupporting
confidence: 58%
“…42 Our definition of allergic asthma is also supported by a recent publication where 65% of subjects with asthma and ARC were polysensitized. 43 There are few studies of asthma prevalence change over time among adults, but some large studies in Europe 6,9,10,14,24,[44][45][46] and in other countries 11,12 have repeatedly surveyed large enough random samples in the same area, within the same age-span and with the same validated methods. Studies on male Swedish conscripts have shown a continuous increase in the prevalence of asthma from the 1960s to the 1990s (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…However, this phenotype needs to be confirmed also in adolescents and adults, to understand whether these associations are transient or persistent along the life course. In a previous analysis in adults from the Epidemiological study of the Genetics and Environment of Asthma, bronchial hyperresponsiveness and atopy—EGEA study, first evidence was provided that polysensitization is associated with multimorbid asthma and rhinitis . However, the analysis was limited by the use of allergen extracts which represent mixtures of source‐specific genuine allergen molecules and cross‐reactive allergens so that a true discrimination of co‐ and cross‐sensitization could not be made and by the fact that only a limited number of allergen extracts could be tested by skin prick testing.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Clinical and Experimental Allergy has also included reports on sensitization patterns for rhinitis and asthma multimorbidity from the EGEA study, 67 an association between DNA methylation of Th2 lineage determinants of genes at birth and later allergic outcomes in the EpiGene consortium 68 The antigen-specific CD4+ Th2 T cell response is thought to be mediated by DC presentation of pollen allergens to naïve CD4+ T cells in the draining lymph nodes. 70,73 Critical steps for the DC-CD4+ type 2 cell polarization is the interaction of co-stimulatory molecules (CD28 and CD80/CD86; OX40L and OX40) between antigen-presenting cells (APCs) and T cells.…”
Section: Other Epidemiological Highlightsmentioning
confidence: 99%
“…Finally, Clinical and Experimental Allergy has also included reports on sensitization patterns for rhinitis and asthma multimorbidity from the EGEA study, 67 an association between DNA methylation of Th2 lineage determinants of genes at birth and later allergic outcomes in the EpiGene consortium 68 and antigen-specific CD4+ Th2 T cell response. 70,71 The ILC2-and CD4+ Th2 cell-derived type 2 cytokines IL-4, IL-5, IL-9 and IL-13…”
Section: Other Epidemiological Highlightsmentioning
confidence: 99%